Figurative Language in Short Story “The Story of An Hour” by Kate Chopin (Jurnal Pustaka, 2026)
This study aimed to analyze the various types of figurative language present in Kate Chopin’s short story “The Story of An Hour”. It employed descriptive qualitative research techniques. The data analyzed stemmed from multiple sentences within the short story, utilizing content analysis  as the primary method. The collected data comprised words and sentences reflecting distinct language style identified from “The Story of An Hour”. This data collection followed a purposive technique, considering spesific langauge style criteria. The researcher utilized qualitative research methods to examine the data extrected from “The Story of An Hour”. The findings revealed a total of 5 figurative languages in Kate Chopin’s short story, including simile, metaphor, personification, metonymy, and symbol.
Keywords: short story; figurative language; American English literature